Bi25FeO40 microspheres loading on g-C3N4 for high efficiency pollutants photodegradation - Nguyen, Xuan Sang (International Journal of Environment, Agriculture and Biotechnology, 2023)
Bi25FeO40/g-C3N4 composites were synthesized for dechlorination of 2-chlorophenol (2-CP). The characteristic of the obtained products was studied using the X-ray diffraction (XRD), (FESEM) scanning electron microscopy, UV-vis reflectance. The effects of g-C3N4 content, photocatalyst dosage, solution pH, H2O2 on the dechlorination efficiency were investigated, in addition to the reusability of the nanocomposites. The results showed that increasing content of Bi25FeO40 in nanocomposites, from 10 to 30 wt.%, greatly increased the dechlorination efficiency. Bi25FeO40/g-C3N4 20wt.% and initial pH below 6.0 was the optimal conditions for the catalytic dechlorination of 2-CP. About 94.5% of 2-CP were completely removed after 150 minutes reaction at initial pH value of 6.0. The composites were easily separated from the solution by an applied magnetic field. The removal efficiency of 2-CP slightly decreased to 90% when the catalyst was reused in 4 runs. Therefore, Bi25FeO40/g-C3N4 composites can be considered as a promising method for remediation of pollution by 2-CP.